ISLAM DAN SOSIALISME (Telaah atas Pemikiran Ali Syariati) - Nurrochman, Nurrochman (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2014)
AbstractAli Shariati, as it is known, is a key figure behind the Iranian revolution. In linewith the thinking Hanafi and Engineer, Shariati comes with the embodiment ofthe spirit of a just social system. He was a great orator and a writer profilik. Inthe early days of the Iranian revolution, the classroom is always filled by aShariati college students who want to listen to his revolutionary ideas. Similarly,his works. Although sometimes seem provocative, but Shariati's writings can notbe denied has become a kind of detonating the Iranian revolution. Shariati wasable to stand in the middle of these two poles, Islam (Shia) on the one hand and Marxism on the other. He shrewdly combining the two, and then give birth to an idea of Islamic socialism. This paper is framed to elaborate further thought Ali Shariati primarily on the concept of Islamic socialism. Posts will be limited to the three principal discussions, namely, how the concept of Islamic socialism Ali Shariati, is there any influence of Marxism in Islamic thought possible Shariati and juxtaposed with the classical teachings of Marxism?Keywoard: Islam, sosialisme, marxisme, kiri Islam